Tomsk “Museum Quarter” Project and Increasing of Well-Being of Older People; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Kolodiy N. A. Nataliya Andreevna; Agranovich V. B. Viktoriya Borisovna; Goncharova N. A. Natalya Aleksandrovna; Chaika (Chayka) Yu. A. Yuliya Aleksandrovna (2017, 2017)
Title screen